Right ventricular and atrial functions in patients with nonischemic dilated cardiomyopathy - ÇİNÇİN, AHMET ALTUĞ; ÖZBEN SADIÇ, BESTE; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT (SPRINGER WIEN, 2015)
The aim of this study was to assess the right ventricular and right atrial functions in patients with nonischemic dilated cardiomyopathy by novel echocardiographic measures. In all, 40 patients with nonischemic dilated cardiomyopathy and 26 healthy subjects were consecutively included. Left ventricular, right ventricular, and right atrial functions were assessed by tissue Doppler imaging and two-dimensional speckle tracking echocardiography. Right ventricular systolic dysfunction was accepted moderated to severe when tissue Doppler peak systolic velocity of tricuspid lateral annulus was < 9 cm/s. In all, 18 of the 40 nonischemic dilated cardiomyopathy patients had peak systolic velocity of tricuspid lateral annulus < 9 cm/s and had significantly lower right ventricular free wall basal segment longitudinal strain, displacement, and right atrial functions assessed by speckle tracking echocardiography. Left ventricular tissue Doppler systolic velocity, global longitudinal and circumferential strain values were also lower in patients with moderated to severe right ventricular systolic dysfunction. Receiver operating characteristic analysis was preformed to assess the utility of right ventricular free wall basal segment longitudinal strain to predict right ventricular systolic dysfunction (peak systolic velocity < 9 cm/s). The cut off value for predicting right ventricular systolic dysfunction was -aEuro parts per thousand 20 % with a sensitivity of 72% and specificity of 73% (AUC: 0.793; p = 0.002; 95 % confidence interval: 0.645-0.941). Right ventricular systolic function is impaired in nonischemic dilated cardiomyopathy patients. Two-dimensional speckle tracking echocardiography represents a promising noninvasive method to evaluate right ventricular and atrial function in this patient group.
Keywords: Nonischemic dilated cardiomyopathy; Right ventricular function; Right atrial function; Speckle tracking echocardiography; Tissue Doppler imaging; CARDIAC RESYNCHRONIZATION THERAPY; 2-DIMENSIONAL SPECKLE TRACKING; OBSTRUCTIVE PULMONARY-DISEASE; ACUTE MYOCARDIAL-INFARCTION; SYSTOLIC HEART-FAILURE; BUNDLE-BRANCH BLOCK; EUROPEAN-ASSOCIATION; MAGNETIC-RESONANCE; AMERICAN-SOCIETY; ANNULAR MOTION